Radiation shielding glass with zinc-barium-borosilicate composition

By developing zinc-barium borosilicate glass, using hard borosilicate and other materials to replace lead-based materials, and adding gadolinium oxide and bismuth oxide, the toxicity and transparency problems of existing radiation shielding materials have been solved, and a transparent radiation shielding effect has been achieved, which is suitable for medical diagnostic centers and other fields.

CN120731192APending Publication Date: 2025-09-30GUROK HLDG BV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280060282.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Existing radiation shielding materials such as lead and heavy concrete are toxic, costly, and opaque, and cannot meet the transparency requirements of medical diagnostic centers. Existing alternative materials such as lead oxide glass are costly and the raw materials are difficult to obtain.

Method used

Using zinc-barium borosilicate glass, by using colemanite, barite, silica sand, zinc oxide and other materials instead of lead-based materials, and adding gadolinium oxide and bismuth oxide, transparent radiation shielding glass is developed to prevent harmful radiation such as X-rays, gamma rays and neutrons.

Benefits of technology

It provides a transparent radiation shielding effect, reduces harm to humans and the environment, is cost-effective, and is suitable for use in medical diagnostic centers and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004728065890000091
    Figure BDA0004728065890000091
  • Figure BDA0004728065890000101
    Figure BDA0004728065890000101
  • Figure BDA0004728065890000111
    Figure BDA0004728065890000111
Patent Text Reader

Abstract

The invention relates to the production of radiation-shielding zinc-barium-borosilicate glass materials, in particular for X-rays and / or gamma-rays and / or fast neutrons and the like, from readily available, low-cost and abundant available starting materials by means of uniquely designed glass compositions. Sodium oxide (Na2O), silicon dioxide (SiO2), boron oxide (B2O3), calcium oxide (CaO), barium oxide (BaO), zinc oxide (ZnO), bismuth oxide (Bi2O3), gadolinium oxide (Gd2O3) and cerium oxide (CeO2) are used in particular, when mixed, a satisfactory and effective shielding effect against X-rays and / or gamma-rays and / or fast neutrons and the like is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to radiation shielding glass containing sodium oxide (Na2O), silicon dioxide (SiO2), boron oxide (B2O3), calcium oxide (CaO), barium oxide (BaO), zinc oxide (ZnO), bismuth oxide (Bi2O3), gadolinium oxide (Gd2O3) and cerium oxide (CeO2), which can be used in aerospace and / or agriculture and / or sterilization fields according to the needs in the field of radiation shielding, in particular in areas such as medical diagnostic centers equipped with X-ray and / or PET / CT and similar equipment, and with scattering emitted from high-level energy sources such as X-rays and / or gamma rays and / or neutrons. Background Art

[0002] With the development of technology in recent years, the number of waves, rays and / or the like emitted from various sources, such as electronic devices, has been increasing. Depending on the duration and dose of exposure, this can reach a point where it threatens human health in a negative way. In particular, high-energy waves, rays and / or the like, such as X-rays and / or gamma rays and / or neutrons, have such a harmful effect on human health that they risk directly damaging the key bonds of biological cells. However, they can also lead to health problems in the form of DNA mutations, dry eyes and skin burns. In order to reduce and / or eliminate these harmful health consequences, a number of protective materials are used, such as metallic lead, concrete and / or the like.

[0003] Lead material, which is often preferred among the preferred alternative materials to overcome radiation, has serious negative consequences for both humans and the environment due to its toxic effects. In addition, low neutron absorption capacity and lack of transparency are another disadvantage of lead-based materials.

[0004] To mitigate the damaging effects of radiation-induced non-ionizing emissions, heavy concrete-based materials with varying heavy aggregate additions and varying thickness factors are widely used to reduce the scattering of high-energy radiation, such as X-rays, gamma rays, and / or neutrons. However, major technical challenges are compositional variations during application and phase formation due to time, temperature, and similar factors, as well as the risk of crack formation during operation. Furthermore, their opaque appearance makes them impractical for use in applications where visibility is essential.

[0005] Metallic lead and heavy concrete materials are both prime examples of applications known in the art. However, as mentioned, their use is limited because they lack a transparent appearance. In particular, these materials cannot be used in areas with inspection door openings, which are essential within the framework of room design standards. From this perspective, different types of glass with various oxide compounds have been developed to reduce and / or eliminate the effects of high-energy scattering, such as X-rays, gamma rays, and / or neutrons.

[0006] In order to reduce and / or eliminate the effects of high energy scattering such as X-rays and / or gamma rays and / or neutrons, lead oxide based glass materials were first developed. The high density (9.53 g / cm 3 ) is intended to suppress incident emission scattering. However, while technically successful glasses have been produced, alternatives have come to the fore due to the toxic effects of lead oxide compounds on both human health and environmental conditions.

[0007] As for alternative glass systems, although glass types based on tellurium oxide, germanium oxide, and vanadium oxide have been studied in the literature, they have not yet been transformed into commercial products. This is due to the unavailability of raw material sources, their unaffordability in terms of cost, and the fact that the technology is not considered suitable within the scope of known production methods.

[0008] There are studies in the literature on radiation shielding materials.

[0009] Patent application number 2018 / 09709 relates to radiation-shielding Er2O3-doped borosilicate glass, which can be used as window glass or exterior cladding in buildings, as well as in the screens of radiation-emitting devices such as computers, mobile phones, and TVs. The authors determined the shielding properties of the glass as a result of doping it with erbium oxide at varying ratios, and found the optimal doping.

[0010] In patent application number 2018 / 09707, radiation shielding CeO2-doped borosilicate glass was presented as an invention. As a result of doping cerium oxide at varying ratios, indicators of shielding performance were extracted, and the doping with the best performance was found.

[0011] European Patent Application No. EP1939147A1 relates to radiation shielding glass and methods for manufacturing the same. The glass composition comprises, by weight, 10% to 35% SiO2, 55% to 80% PbO, 0% to 10% B2O3, 0% to 10% Al2O3, 0% to 10% SrO, 0% to 10% BaO, 0% to 10% Na2O, and 0% to 10% KO, and has a total light transmittance of 50% or greater at a wavelength of 400 nm and a thickness of 10 mm. Another patent application, US Pat. No. 10035725B2, discloses X-ray and gamma-ray shielding glass and methods for manufacturing such glass. The glass compositions discussed include, by weight, 0% to 35% SiO2, 60% to 70% PbO, 0% to 8% B2O3, 0% to 10% Al2O3, 0% to 10% Na2O, 0% to 10% KO, 0% to 0.3% As2O3, 0% to 2% Sb2O3, 0% to 6% BaO, and 0.05% to 2% ZrO2. However, these documents contain no information regarding zinc-barium borosilicate glass materials.

[0012] In order to overcome the above-mentioned problems with alternative radiation shielding materials that are commercially and routinely used in the art, there is a need for alternative glass compositions that are more cost-effective than readily available raw materials, that protect against high energy scattering, such as X-rays and / or gamma rays and / or neutrons, etc., without having deleterious effects on humans and the environment.

[0013] Therefore, due to the above-mentioned shortcomings and deficiencies of existing solutions, developments in the relevant technical fields have become necessary. Summary of the Invention

[0014] The present invention is inspired by the existing inventions and aims to solve the above problems.

[0015] The primary object of the present invention is to provide a lead oxide-free zinc barium borosilicate glass composition specifically designed to prevent high energy scattering, such as X-rays and / or gamma rays and / or neutrons, by minimizing the negative impacts on the environment and human health caused by lead oxide-containing radiation shielding materials used in the art.

[0016] An object of the present invention is to provide an improved transparent zinc barium borosilicate glass material having no harmful effects on humans and the environment. The glass material comprises bismuth oxide (Bi2O3), gadolinium oxide (Gd2O3) and cerium oxide (CeO2).

[0017] Another object of the present invention is to develop a glass material that uses readily available raw materials, is highly cost-effective and is highly amenable to forming methods.

[0018] For this purpose, a process for producing zinc-barium borosilicate glass is applied by selecting starting raw materials of colemanite, barite, silica sand, zinc oxide, soda ash, bismuth oxide, gadolinium oxide, and cerium oxide, instead of the always preferred lead-based materials and / or glass systems and / or concretes with different aggregates. Colemanite, which is a calcium borate, was selected for use due to its neutron-capturing and / or absorbing and / or damping properties.

[0019] In our invention, barite (a mineral composed of barium sulfate) is preferably used to attenuate X-rays, gamma rays, and / or neutrons. Zinc oxide is also used to improve optical properties or radiation damping (attenuation) capabilities. Silica sand (a source of silicon dioxide) is selected to provide the structure of the glass system. Soda ash composed of sodium carbonate is also preferred to lower the melting point of the glass system of the present invention.

[0020] In order to achieve the above-mentioned objectives, the present invention is a radiation shielding zinc-barium-borosilicate glass, which allows a transparent appearance to be provided in different areas where radiation-induced ionizing rays will appear, particularly in medical diagnostic centers and research institutions, and which can also be used for the purpose of preventing harmful radiation from X-rays and / or gamma rays and / or fast neutrons, etc., characterized in that it includes: adding gadolinium oxide (Gd2O3) and / or bismuth oxide (Bi2O3) and / or cerium oxide (CeO2) to zinc-barium-borosilicate (ZnO-BaO-B2O3-SiO2) glass powder.

[0021] The structure and characteristic features and all advantages of the present invention will be more clearly understood through the drawings given below and the detailed description written with reference to these drawings, and therefore should be evaluated by considering these drawings and the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the production process of the radiation shielding zinc barium borosilicate glass material of the present invention.

[0023] Description of Reference Numerals

[0024] 1. Raw material formula

[0025] 2. Weighing unit

[0026] 3. Raw material mixer

[0027] 4. Melting furnace

[0028] 5. Forming mold

[0029] 6. Annealing furnace

[0030] 7. Glass products DETAILED DESCRIPTION

[0031] In this detailed description, a preferred embodiment of the radiation shielding zinc-barium-borosilicate glass (ZnO-BaO-B2O3-SiO2) of the present invention is described only for the purpose of better understanding the subject matter.

[0032] The present invention is a radiation-shielding zinc-barium-borosilicate glass that allows for transparent appearance in various areas where radiation-induced ionizing radiation may be present, particularly in medical diagnostic centers and research institutions, and can also be used to prevent harmful emissions from X-rays and / or gamma rays and / or fast neutrons, etc. The zinc-barium-borosilicate (ZnO-BaO-B2O3-SiO2) glass includes additions of gadolinium oxide (Gd2O3) and / or bismuth oxide (Bi2O3) and / or cerium oxide (CeO2). The glass in question is used in applications such as bone densitometry, mammography, dental X-rays, X-ray imaging, magnetic resonance (MR), PET / CT, gamma knives, and in the fields of aerospace, defense, food, and agriculture, without being limited to those mentioned.

[0033] The radiation shielding glass includes the following components as range values: 0.01 mol% to 15 mol% of Na2O, 0.01 mol% to 5 mol% of MgO, 0.01 mol% to 5 mol% of Al2O3, 15 mol% to 75 mol% of SiO2, 0.01 mol% to 30 mol% of B2O3, 0.01 mol% to 13 mol% of CaO, 0.01 mol% to 35 mol% of BaO, 0.01 mol% to 2 mol% of TiO2, 0.01mol% to 5mol% SrO, 0.01mol% to 15mol% ZnO, 0.01mol% to 4mol% Li2O, 0.01mol% to 10.00mol% Gd2O3, 0.01mol% to 10mol% Bi2O3, 0.01mol% to 10mol% CeO2, 0.01mol% to 5mol% Sb2O3 and 0.001mol% to 0.10mol% Fe2O3.

[0034] The radiation shielding glass of the present invention has a melting temperature value higher than 1000° C. and lower than 1400° C. and an annealing start temperature value higher than 400° C. and lower than 700° C. It also has an annealing time ranging from 80 minutes to 120 minutes.

[0035] The radiation shielding glass of the present invention has a thickness ranging from 3 mm to 100 mm. The glass density is 3.25 g / cm³ or greater, and the Young's modulus is 75 GPa or greater. The radiation shielding glass has a refractive index of 1.76 or greater, and a thermal expansion coefficient of at most 8.75 × 10⁻⁶ / K.

[0036] The radiation shielding glass should have the following size and number in terms of the number of gas inclusions (habbees, cracks and / or spots).

[0037] - For diameters from 0.001mm to 0.01mm, 15 pieces / 30g glass,

[0038] - For diameters from 0.01mm to 0.1mm, 10 pieces / 30g glass,

[0039] -For diameters of -0.1mm and larger, 5 pcs / 30g glass.

[0040] The subject of the present invention is a radiation shielding glass having a transmittance of 50% and more at a wavelength of 400 nm and a thickness of at least 10 mm, and a transmittance of 75% and more at a wavelength of 550 nm and a thickness of at least 10 mm.

[0041] The radiation shielding glass of the present invention has silica sand, quartz, quartzite, barite, barium carbonate, colemanite, ulexite, soda ash, albite, limestone, dolomite, spodumene, sodium nitrate, sodium sulfate, zinc oxide, gadolinium oxide, gadolinium sulfate, bismuth oxide, bismuth nitrate, cerium oxide, antimony trioxide, strontium carbonate, anthracite, zinc selenite and cobalt oxide as starting raw materials.

[0042] The chemical composition of the raw materials is crucial for preparing glass blends. Therefore, the present invention utilizes high-purity raw materials with satisfactory chemical composition characteristics. In this context, high purity means having at least 99.00% of the main components and a maximum of 1000 ppm of Fe₂O₃. The raw materials are carefully weighed within limited tolerances. Based on the predetermined amounts of each raw material, the glass tolerance is set to a maximum of 0.01% of the weighed amount.

[0043] Impurities such as Fe2O3 (iron oxide) and / or similar impurities (e.g., Cr2O3) contained in the raw materials used in the glassmaking process can cause problems such as melt coloration or similar glass defects (e.g., gas bubbles). The transparency of glass products is important for effective radiation shielding, which controls the discoloration produced by the iron oxide value. This means that iron oxide causes a natural green tint in the glass, resulting in poor visibility. To produce glass products that provide adequate transparency, the amount of iron oxide should not exceed 1000 ppm.

[0044] Furthermore, transparent glass products are at risk of visually revealing some defects, including scratches, bubbles, etc. In order to achieve significant quality in glass products, it is very important to remove defects.

[0045] Density is a key parameter that is monitored in a specific manner and is the result of the optimization of the patented mixture in question. The higher the density of the glass system, the higher the performance of the shielding glass. The density achieved for the glass composition variants is generally considered to be greater than 2.75 g / cm 3 Up to 3.00g / cm 3 , preferably 3.00g / cm 3 Up to 3.25g / cm 3 , more preferably 3.25g / cm 3 Up to 3.50g / cm 3 , and preferably greater than 3.50g / cm 3 As a result of this study, it was determined that the density of the glass was greater than 3.25 g / cm 3 .

[0046] The radiation shielding glass material of the present invention comprises a novel glass composition in the following ranges of molar percentages: 0.01 mol% to 15.00 mol% of Na2O, 0.01 mol% to 5.00 mol% of MgO, 0.01 mol% to 5.00 mol% of Al2O3, 15.00 mol% to 75.00 mol% of SiO2, 0.01 mol% to 30 mol% of B2O3, 0.01 mol% to 13 mol% of CaO, 0.01 mol% to 35 mol% of BaO, 0.01 mol% to 5.00 mol% of 2.00 mol% TiO2, 0.01 mol% to 5.00 mol% SrO, 0.01 mol% to 15.00 mol% ZnO, 0.01 mol% to 4.00 mol% Li2O, 0.01 mol% to 10.00 mol% Gd2O3, 0.01 mol% to 10.00 mol% Bi2O3, 0.01 mol% to 10 mol% CeO2, 0.01 mol% to 5 mol% Sb2O3, and 0.001 mol% to 0.10 mol% Fe2O3. Furthermore, cerium oxide, a refining agent in the range of 100 ppm to 5,000 ppm, can be used to remove glass defects such as stringiness, bubbles, and the like. In the present invention, the absence of other toxic refining agents, such as arsenic trioxide, is preferred. Furthermore, the amount of iron oxide (which naturally produces a green color in medium glass products and is also responsible for the low visibility) is strictly controlled during the melting process of the raw material mixture.

[0047] Sodium dioxide Sodium dioxide is a component that improves the moldability of the glass composition and lowers its melting point. The sodium dioxide content is 0 to 15 mol%, preferably 5 to 10 mol%, and more preferably 10 to 15 mol%. If the sodium dioxide content exceeds 15 mol%, high-temperature viscosity becomes uncontrollable, resulting in insufficient radiation shielding ability.

[0048] Silicon dioxide Silica is a structural component of the glass composition and is also the primary primary forming agent of the present invention. Its content herein is 15 to 75 mol%, preferably 55 to 60 mol%, and more preferably 60 to 75 mol%. If the silica content exceeds 75 mol%, the melting point of the glass composition increases, resulting in uncontrollable viscosity characteristics. Conversely, if the silica content is less than 15 mol%, the primary forming agent becomes thermally unstable.

[0049] Boron oxide Boron oxide is a component that, under appropriate conditions, not only lowers the melting point of the glass composition but also improves the thermal stability of the glass structure by correspondingly altering the glass structure. The boron oxide content is 0 to 30 mol%, preferably 0.1 to 5 mol%, and more preferably 5 to 10 mol%. If the boron oxide content is significantly higher than 30 mol%, the thermal stability of the glass product in question deteriorates.

[0050] Calcium dioxide This component improves the chemical resistance of the glass composition, particularly its water resistance. The calcium oxide content is 0 to 13 mol%, preferably 0.1 to 4 mol%, and more preferably 4 to 13 mol%. A calcium oxide content exceeding 13 mol% can hinder formability, resulting in insufficient radiation shielding against X-rays, gamma rays, and / or fast neutrons.

[0051] barium oxide Due to its high atomic number, barium is a preferred component for improving the radiation performance of glass materials. The barium oxide content is 0 mol% to 35 mol%, preferably 0.1 mol% to 15 mol%, and more preferably 15 mol% to 35 mol%. If the barium oxide content exceeds 30 mol%, the glass becomes thermally unstable.

[0052] zinc oxide It is a component that improves glass-forming properties and also provides higher UV transparency. The zinc oxide content is 0 mol% to 15 mol%, preferably 0.1 mol% to 4 mol%, more preferably 4 mol% to 8 mol%, and even more preferably 8 mol% to 12 mol%. When the zinc oxide content exceeds 15 mol%, the radiation shielding properties of the glass in question are adversely affected.

[0053] Gadolinium oxide Used as a shield against X-rays and / or gamma rays and / or fast neutrons etc. Gadolinium oxideHigh density values ​​improve radiation shielding properties. The gadolinium oxide content is 0 to 10 mol%, preferably 0.1 to 1 mol%, more preferably 1 to 3 mol%, and even more preferably 3 to 6 mol%. If the gadolinium oxide content exceeds 10 mol%, the glass loses its transparency in terms of color.

[0054] Bismuth oxide Due to its high atomic number, bismuth improves the radiation protection properties of glass systems. The bismuth oxide content is 0 to 10 mol%, preferably 0.1 to 1 mol%, more preferably 1 to 3 mol%, and even more preferably 3 to 6 mol%. If the bismuth oxide content exceeds 10 mol%, the glass becomes thermally unstable.

[0055] Cerium oxide It is a component used as a fining agent in glass systems. The cerium oxide content is 1,000 ppm to 5,0000 ppm, preferably 1,000 ppm to 3,000 ppm. If the cerium oxide content is less than 1,000 ppm, the glass product may be insufficiently refined, resulting in the glass product containing bubbles.

[0056] Any other components (eg Li2O, K2O) may be added up to 10 mol % as long as the properties of the glass are not impaired.

[0057] Glass Embodiments of the Invention

[0058] In a practical embodiment of an improved glass composition specifically designed for attenuation of X-rays and / or gamma rays and / or fast neutrons, etc., the following blended mixtures are prepared, expressed in mole percentages. These blends can vary depending on the chemical properties of the raw materials selected within the scope of the present invention. The utilization of the raw materials is variable, both physically and chemically, within predetermined tolerances, in terms of the amounts obtained.

[0059] Figure 1Shown is a production process diagram. First, the selected raw materials are prepared in a manner such that the selected raw materials have the glass composition listed in each different application and sub-formula. Weighing is carried out according to the tolerance percentage mentioned. After weighing each compound, a mixing process is carried out for 15 to 60 minutes in a porcelain container in a dry environment with alumina balls at a speed range of 250 rpm to 500 rpm by a grinder and / or a mechanical mixer to form a uniform mixture. After obtaining a uniform mixture, the prepared glass pile is melted in a resistance lift melting furnace and / or a gold-platinum alloy crucible without any atmosphere control. For the melting temperature, any temperature value between 1000°C and 1400°C can be selected. The holding time at the melting temperature is 60 to 180 minutes. After obtaining a glass melt and the waiting time is over, the glass melt is preferably immediately poured into a graphite mold or placed in a gold-platinum alloy crucible for 5 to 10 minutes at room temperature. The glass products obtained by these two methods are then taken out together with the mold containing the glass melt, or taken out from the gold-platinum alloy crucible, and placed in an annealing furnace heated to any temperature between 400° C. and 700° C. for any time between 80 minutes and 120 minutes for stress relief annealing, and after the waiting period is over, the glass product is taken out from the annealing container and / or furnace to obtain the final glass product.

[0060] In Table 1 below, Example 1 provides a glass composition for effectively blocking radiation, such as X-rays, gamma rays, and / or fast neutrons. The code OR represents the base formulation. The code BA indicates an increase in the amount of barium oxide (BaO). The code BO is associated with an increase in the amount of boron oxide (BO). The addition of BaO and BO improves the damping ability of the base glass formulation (OR glass) against X-rays, gamma rays, and / or fast neutrons.

[0061] Table 1: Example 1: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons

[0062]

[0063] First, the selected raw materials are prepared in such a way that they have the glass compositions listed in the various applications and sub-formulas. They are weighed according to the tolerance percentages mentioned. After weighing each compound, a mixing process is carried out in a porcelain container with a drying medium having alumina balls at a speed range of 250 rpm to 500 rpm using a grinder and / or a mechanical mixer for 15 to 60 minutes to form a uniform mixture. After obtaining a uniform mixture, the prepared glass is piled in a gold-platinum alloy crucible in a resistance box and / or lift melting furnace and melted without any atmosphere control. The melting temperature is any temperature between 1000°C and 1400°C. As the waiting time at the melting temperature, any temperature value between 60 minutes and 180 minutes is selected. After obtaining a glass melt and the waiting time of the melt is over, the glass melt is preferably immediately poured into a graphite mold or kept in a gold-platinum alloy crucible at room temperature for 5 to 10 minutes to obtain a glass product. The glass products obtained by these two methods are then taken out from the mold with the glass melt or from the gold-platinum alloy crucible and placed in an annealing furnace heated to any temperature between 400° C. and 700° C. for any time between 80 minutes and 120 minutes for stress relief annealing. After the waiting time is over, the glass product is taken out from the annealing container and / or furnace and the final glass product is successfully obtained.

[0064] For the concrete assembly of Example 1, the radiation shielding glass has a linear attenuation coefficient value of 0.217 cm-1 and greater at an energy level of 662 keV; a linear attenuation coefficient value of 0.155 cm-1 and greater at an energy level of 1173 keV; and a linear attenuation coefficient value of 0.150 cm-1 and greater at an energy level of 1332 keV.

[0065] Table 2 below shows Example 2: Glass composition for effectively blocking radiation such as X-rays, gamma rays, and / or fast neutrons. The code BB represents the base formulation. The code BBGd indicates the amount of added gadolinium oxide (Gd2O3). The code BBBi indicates the amount of added bismuth oxide (Bi2O3). The code BBCe indicates the amount of added cerium oxide (CeO2). The addition of Gd2O3, Bi2O3, and CeO2 improves the damping capability of the base glass formulation BB glass against X-rays, gamma rays, and / or fast neutrons.

[0066] Table 2 Example 2: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons

[0067]

[0068] First, the raw materials selected are prepared in a manner such that the raw materials selected have the glass compositions listed in the various applications and sub-formulas. Weigh according to the tolerance percentages mentioned. After weighing each compound, a mixing process is carried out for 15 to 60 minutes in a dry environment with alumina balls in a porcelain container using a grinder and / or a mechanical mixer at a speed range of 250 rpm to 500 rpm to form a uniform mixture. After obtaining a uniform mixture, the prepared glass pile is melted in a resistance lift melting furnace and / or a gold-platinum alloy crucible without any atmosphere control. The melting temperature is selected to be any temperature between 1000°C and 1400°C. The waiting time at the melting temperature is selected to be between 160 and 180 minutes. After obtaining a glass melt and the waiting time of the melt is over, the glass melt is preferably immediately poured into a graphite mold or kept in a gold-platinum alloy crucible for 5 to 10 minutes at room temperature to obtain a glass product. The glass products obtained by these two methods are then taken out from the mold with the glass melt or from the gold-platinum alloy crucible and placed in an annealing furnace heated to any temperature between 400° C. and 700° C. for any time between 80 minutes and 120 minutes for stress relief annealing. After the waiting time is over, the glass product is taken out from the annealing container and / or furnace and the final glass product is successfully obtained.

[0069] For the embodiment of Example 2, the radiation shielding glass of the present invention has a linear attenuation coefficient value of 0.254 cm-1 and greater at an energy level of 662 keV; a linear attenuation coefficient value of 0.175 cm-1 and greater at an energy level of 1173 keV; and a linear attenuation coefficient value of 0.165 cm-1 and greater at an energy level of 1332 keV.

[0070] Table 3 below shows Example 3: Glass compositions for effectively blocking radiation such as X-rays, gamma rays, and / or fast neutrons. The codes BBGd1, BBGd2, and BBGd3 represent increasing amounts of gadolinium oxide (Gd2O3). The addition of Gd2O3 improves the ability to dampen X-rays, gamma rays, and / or fast neutrons.

[0071] Table 3 Example 3: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons

[0072]

[0073] The linear attenuation coefficient (μ) values ​​obtained for Examples 1, 2, and 3 are given in cm-1 in Tables 4, 5, and 6. Three different gamma-ray energy levels, 662 keV, 1173 keV, and 1332 keV, were selected as sample energy levels. Gamma-ray spectrometry was used in the measurement method. NaI was used as the detector. Co60 and Cs137 were selected as the radiation sources.

[0074] Table 4 Linear attenuation loss (μ) values ​​(cm) for Example 1 at 662keV, 1173keV and 1332keV -1 )

[0075]

[0076] Table 5 Linear attenuation loss (μ) values ​​(cm) for Example 2 at 662keV, 1173keV and 1332keV -1 )

[0077]

[0078] Table 6 Linear attenuation coefficient (μ) values ​​(cm) for Example 3 at 662keV, 1173keV and 1332keV -1 )

[0079]

Claims

1. The present invention relates to radiation shielding zinc-barium-borosilicate glass, which allows providing a transparent appearance in different areas where radiation-induced ionizing rays will appear, in particular in medical diagnostic centers and research institutions, and the radiation shielding zinc-barium-borosilicate glass can also be used to protect against harmful radiation from X-rays and / or gamma rays and / or fast neutrons, etc., characterized in that Gadolinium oxide (Gd2O3) and / or bismuth oxide (Bi2O3) and / or cerium oxide (CeO2) are added to zinc-barium-borosilicate (ZnO-BaO-B2O3-SiO2) glass powder.

2. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that % to 15 mol% of Na2O, 0.01 mol% to 5 mol% of MgO, 0.01 mol% to 5 mol% of Al2O3, 15 mol% to 75 mol% of SiO2, 0.01 mol% to 30 mol% of B2O3, 0.01 mol% to 13 mol% of CaO, 0.01 mol% to 35 mol% of BaO, 0.01 mol% to 2 mol% of TiO2, 0.01 mol% to 5 mol% SrO, 0.01 mol% to 15 mol% ZnO, 0.01 mol% to 4 mol% Li2O, 0.01 mol% to 10.00 mol% Gd2O3, 0.01 mol% to 10 mol% Bi2O3, 0.01 mol% to 10 mol% CeO2, 0.01 mol% to 5 mol% Sb2O3 and 0.001 mol% to 0.10 mol% Fe2O3.

3. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: Used in applications such as bone densitometry, mammography, dental X-ray, X-ray imaging, magnetic resonance imaging (MRI), PET / CT, gamma knife, and in the fields of space, defense, food and agriculture, and not limited to those mentioned.

4. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The values ​​of Fe2O3 and Cr2O3 components were 1000 ppm or less.

5. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The radiation shielding zinc-barium-borosilicate glass has a melting temperature higher than 1000°C and lower than 1400°C.

6. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The radiation shielding zinc-barium-borosilicate glass has an annealing initiation temperature higher than 400°C and lower than 700°C.

7. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The annealing time is in the range of 80 minutes to 120 minutes.

8. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The glass thickness is in the range of 3 mm to 100 mm.

9. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: In terms of the number of gas inclusions (pores and / or bubbles), the radiation-shielding zinc-barium-borosilicate glass has 15 gas inclusions per 30 grams of glass with a diameter of 0.001 mm to 0.01 mm, 10 gas inclusions per 30 grams of glass with a diameter of 0.01 mm to 0.1 mm, and 5 gas inclusions per 30 grams of glass with a diameter of 0.1 mm or more.

10. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The glass density is 3.25 g / cm 3 and bigger.

11. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The Young's modulus value is 75 GPa and greater.

12. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The refractive index is 1.76 and greater.

13. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The transmittance is 50% or more at a wavelength of 400 nm and a thickness of at least 10 mm.

14. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The transmittance is 75% or greater at a wavelength of 550 nm and a thickness of at least 10 mm.

15. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The thermal expansion coefficient is not greater than 8.75×10 -6 / K.

16. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO and Fe2O3, the radiation shielding zinc-barium-borosilicate glass has a 0.217 cm2 / cm3 / cm2 energy level at 662 keV. -1 and larger linear attenuation coefficient values.

17. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO and Fe2O3, the radiation shielding zinc-barium-borosilicate glass has a 0.155 cm3 / s energy level at 1173 keV. -1 and larger linear attenuation coefficient values.

18. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO and Fe2O3, the radiation shielding zinc-barium-borosilicate glass has a 0.150 cm3 / s energy level at 1332 keV. -1 and larger linear attenuation coefficient values.

19. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO, Fe2O3, Gd2O3, Bi2O3 and CeO2, the radiation shielding zinc-barium-borosilicate glass has a 0.254 cm2 / s at the 662 keV energy level. -1 and larger linear attenuation coefficient values.

20. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO, Fe2O3, Gd2O3, Bi2O3 and CeO2, the radiation shielding zinc-barium-borosilicate glass has a 0.175 cm3 / s at the 1173 keV energy level. -1 and larger linear attenuation coefficient values.

21. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO, Fe2O3, Gd2O3, Bi2O3 and CeO2, the radiation shielding zinc-barium-borosilicate glass has a 0.165 cm3 / s at the 1332 keV energy level. -1 and larger linear attenuation coefficient values.

22. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO, Fe2O3 and Gd2O3, the radiation shielding zinc-barium-borosilicate glass has a 0.302 cm2 / s energy level at 662 keV. -1 and larger linear attenuation coefficient values.

23. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO, Fe2O3 and Gd2O3, the radiation shielding zinc-barium-borosilicate glass has a 0.206 cm2 / s energy level at 1173 keV. -1 and larger linear attenuation coefficient values.

24. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: For the components Na2O, SiO2, B2O3, CaO, BaO, ZnO, MgO, Al2O3, SrO, Fe2O3 and Gd2O3, the radiation shielding zinc-barium-borosilicate glass has a 0.171 cm2 / cm3 / s energy level at 1332 keV. -1 and larger linear attenuation coefficient values.

25. The radiation shielding zinc-barium-borosilicate glass according to claim 1, characterized in that: The radiation shielding zinc-barium-borosilicate glass has silica sand, quartz, quartzite, barite, barium carbonate, colemanite, ulexite, soda ash, albite, limestone, dolomite, spodumene, sodium nitrate, sodium sulfate, zinc oxide, gadolinium oxide, gadolinium sulfate, bismuth oxide, bismuth nitrate, cerium oxide, antimony trioxide, strontium carbonate, anthracite, zinc selenite and cobalt oxide as starting raw materials.

Citation Information

Patent Citations

  • Radiation shielding glass and method for manufacture thereof

    EP1939147A1

  • X-ray and gamma-ray shielding glass

    US10035725B2